Dependence between factors of an environmens and a state of the population of the Astrakhan area - I. Yu. Bolotnikov; N. N. Kuryanova; A. G. Serdyukov (Юг России: экология, развитие)
The regional analysis of features of the general death rate in the Astrakhan area for last 25 years is lead. Cases of death behind the instruction of features with revealing intensive and extensive parameters on a floor, age, the reasons of death are analyzed all. For the 25-years period growth of death rate of the population of the Astrakhan area is distinguished, death rate of the man's population prevailed above female. The tendency of increase of mortality rate coefficients in all age groups is noted.